Understanding feeling “high” and its role in medical cannabis patient outcomes - Stith, Sarah S.; Li, Xiaoxue; Brockelman, Franco; Keeling, Keenan; Hall, Branden; Vigil, Jacob M. (Frontiers in Pharmacology, 2023)
Introduction: We measure for the first time the associations between subjective patient experiences of feeling “high” and treatment outcomes during real-time Cannabis flower consumption sessions. Methods: Our study uses data from the mobile health app, Releaf App™, through which 1,882 people tracked the effects of Cannabis flower on a multitude of health conditions during 16,480 medical cannabis self-administration sessions recorded between 6/5/2016 and 3/11/2021. Session-level reported information included plant phenotypes, modes of administration, potencies, baseline and post-administration symptom intensity levels, total dose used, and real-time side effect experiences. Results: Patients reported feeling high in 49% of cannabis treatment sessions. Using individual patient-level fixed effects regression models and controlling for plant phenotype, consumption mode, tetrahydrocannabinol (THC) and cannabidiol (CBD) potencies, dose, and starting symptom level, our results show that, as compared to sessions in which individuals did not report feeling high, reporting feeling high was associated with a 7.7% decrease in symptom severity from a mean reduction of −3.82 on a 0 to 10 analog scale (coefficient = −0.295, p < 0.001) with evidence of a 14.4 percentage point increase (p < 0.001) in negative side effect reporting and a 4.4 percentage point (p < 0.01) increase in positive side effect reporting. Tetrahydrocannabinol (THC) levels and dose were the strongest statistical predictors of reporting feeling high, while the use of a vaporizer was the strongest inhibitor of feeling high. In symptom-specific models, the association between feeling high and symptom relief remained for people treating pain (p < 0.001), anxiety (p < 0.001), depression (p < 0.01) and fatigue (p < 0.01), but was insignificant, though still negative, for people treating insomnia. Although gender and pre-app cannabis experience did not appear to affect the relationship between high and symptom relief, the relationship was larger in magnitude and more statistically significant among patients aged 40 or less. Discussion: The study results suggest clinicians and policymakers should be aware that feeling high is associated with improved symptom relief but increased negative side effects, and factors such as mode of consumption, product potency, and dose can be used to adjust treatment outcomes for the individual patient.